2016
DOI: 10.1039/c6cp00589f
|View full text |Cite
|
Sign up to set email alerts
|

High-field dissolution dynamic nuclear polarization of [1-13C]pyruvic acid

Abstract: [1-(13)C]pyruvate is the most widely used hyperpolarized metabolic magnetic resonance imaging agent. Using a custom-built 7.0 T polarizer operating at 1.0 K and trityl radical-doped [1-(13)C]pyruvic acid, unextrapolated solution-state (13)C polarization greater than 60% was measured after dissolution and rapid transfer to a spectrometer magnet, demonstrating the signal enhancement attainable using optimized hardware. Slower rates of polarization under these conditions can be largely overcome with higher radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
94
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(99 citation statements)
references
References 29 publications
4
94
1
Order By: Relevance
“…The liquid-state 13 C polarization obtained in the present work is severalfold lower than the maximum values obtained by dissolution DNP using the same polarizer and trityl radicals30. The narrower ESR line width of trityl radicals as compared to photo-induced radicals is expected to lead to higher 13 C polarization25, but the main reason for the lower polarization is the sub-optimal radical concentration, which also explains that the build-up time constant is larger than in an optimized PA sample prepared with trityl radical.…”
Section: Discussioncontrasting
confidence: 75%
“…The liquid-state 13 C polarization obtained in the present work is severalfold lower than the maximum values obtained by dissolution DNP using the same polarizer and trityl radicals30. The narrower ESR line width of trityl radicals as compared to photo-induced radicals is expected to lead to higher 13 C polarization25, but the main reason for the lower polarization is the sub-optimal radical concentration, which also explains that the build-up time constant is larger than in an optimized PA sample prepared with trityl radical.…”
Section: Discussioncontrasting
confidence: 75%
“…The frozen glassy UV‐irradiated beads were loaded into a polytetrafluoroethylene sample cup together with frozen droplets of NaOH solution, the volume and concentration of which was calculated to balance the pH to 7 during dissolution. The polytetrafluoroethylene cup was then placed inside a 7T homebuilt polarizer, and the 13 C spins were polarized for 2 hours at 1.0 ± 0.1 K with the microwave frequency set to 196.75 GHz . Using an automated process, the sample was rapidly dissolved in 6 mL D 2 O and transferred within 2 seconds into a remotely controlled phase separator/injection pump, located inside the bore of the MR scanner (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown a trend in which DNP systems at higher field than 3.35 T yielded higher 13 C polarization levels. [20][21][22][23][25][26][27][28] In this work, we describe the development of a 180…”
Section: Introductionmentioning
confidence: 99%